2012
DOI: 10.1016/j.yexmp.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

FAT10 knock out mice livers fail to develop Mallory–Denk bodies in the DDC mouse model

Abstract: Mallory-Denk bodies (MDBs) are aggresomes composed of undigested ubiqutinated short lived proteins which have accumulated because of a decrease in the rate of their degradation by the 26s proteasome. The decrease in the activity of the proteasome is due to a shift in the activity of the 26s proteasome to the immunoproteasome triggered by an increase in expression of the catalytic subunits of the immunoproteasome which replaces the catalytic subunits of the 26s proteasome. This switch in the type of proteasome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…MDB formation may be the result of the reduced activity of the FAT10ylation pathway of protein degradation, causing the proteins to accumulate and form aggresomes (MDBS). The FATylation pathway of protein degradation may be essential for MDB formation, since FAT10 knockout (KO) mice refed DDC failed to form MDBs compared with wild-type mice refed DDC where numerous MDBs were formed [4]. …”
Section: Role Of the Ufmylation And Fat10ylation Pathways To Protementioning
confidence: 99%
“…MDB formation may be the result of the reduced activity of the FAT10ylation pathway of protein degradation, causing the proteins to accumulate and form aggresomes (MDBS). The FATylation pathway of protein degradation may be essential for MDB formation, since FAT10 knockout (KO) mice refed DDC failed to form MDBs compared with wild-type mice refed DDC where numerous MDBs were formed [4]. …”
Section: Role Of the Ufmylation And Fat10ylation Pathways To Protementioning
confidence: 99%
“…It has been demonstrated that the autophagosomal receptor p62/SQSTM1 becomes covalently mono-FAT10ylated at several lysines, and that FAT10 co-localizes with p62 in p62 bodies . Furthermore, FAT10 is involved in the formation of Mallory-Denk bodies, which are aggresome-like structures in hepatocellular carcinoma cells composed of ubiquitylated proteins (French et al, 2012). Additionally, FAT10 decorates autophagy-targeted Salmonella and contributes to Salmonella resistance in mice (Spinnenhirn et al, 2014) (see below).…”
Section: Fat10 In Antigen Processingmentioning
confidence: 99%
“…3,5 UbD 2/2 mice fed DDC cannot form MDBs. 6 SAMUEL FRENCH, M.D. Harbor-UCLA Medical Center Torrance, CA…”
Section: Hepatocyte Levels Of Cd73 Contribute To Mallory-denk Body Fomentioning
confidence: 99%